TINJAUAN TEOLOGIS: DIGITALISASI DAN TRANSFORMASI SPIRITUALITAS KRISTEN - Fira Tando; Heni Kartini Tallu Tondok (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research examines a theological review of the impact of digitalization on the transformation of Christian spirituality. In the digital era, technological advancements have changed the way Christians worship, communicate, and access spiritual resources. The use of social media, prayer apps, and streaming platforms for virtual worship has become an increasingly common phenomenon. However, theological questions arise regarding how digitalization affects Christians' understanding and experience of their spirituality. This review discusses the challenges and opportunities the church faces in response to technological developments, as well as how fundamental Christian principles, such as community and divine presence, remain relevant in the digital world. The study also explores how digitalization can enrich but also potentially diminish the depth and intimacy of believers' relationship with God and with one another. In conclusion, the article offers perspectives on how the church and Christians can wisely adapt to the changing times without compromising the integrity of Christian spirituality